Analysis of external environment of municipal strategic planning: Municipal and regional representations in Brussels - Tatárné Varga, Ivett (Studia Mundi – Economica, 2015)
To improve regional competitiveness with a special regard to large urban zones, and to support sustainable development, the analysis of possible methods and levels of cooperation is a key element.This study is the first publication of a detailed primer research survey conducted among city and regional level representations in the European Union, as part of extended external environmental analysis of municipal strategic planning. The survey and the analysis based on it concentrate on the role of municipal and regional EU representations is Brussels by introducing their main activities, the structure of their relations, their intra-state, extra-state and EU-level political activities. The analysis evaluates both potential possibilities of inter-regional cooperation and increasing of funding absorption, mainly in relation to direct EU funds.As maintaining or potential increase of funding absorption, financing, city and regional marketing are outstanding priorities of strategic planning, the study also introduces the present status of representations in these fields and their participation in EU-funded projects and also, it offers further areas to extend their strategic potential.
Keywords: EU strategy; public sector; strategic planning; external environment